2021
DOI: 10.1155/2021/3418887
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Mesoporous Biochar from Cornstalk for the Chromium (VI) Elimination by Using One-Step Hydrothermal Carbonation

Abstract: Hydrothermal carbon (HTC) was prepared by the one-step hydrothermal method for Cr (VI) removal from wastewater, which was considered a “green chemistry” method. The specific surface area (SBET) of HTC was 85 m2/g with the pore size in range of 2.0–24.0 nm. FT-IR spectra analysis showed that the HTC had abundant chemical surface functional groups. The influence of adsorption parameters such as pH, HTC dosage, Cr (VI) concentration, and contact time on the removal efficiency of Cr (VI) had been investigated. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Furthermore, it was discovered that the estimated qe values for the PSO model and the observed qe values agreed rather well, indicating a superior fit compared to the PFO model. Based on these findings, the PSO model was considered appropriate for explaining the adsorption mechanism and it was determined that the chemisorption mechanism governed the adsorption process, as previously reported [53].…”
Section: Kinetics Studymentioning
confidence: 94%
“…Furthermore, it was discovered that the estimated qe values for the PSO model and the observed qe values agreed rather well, indicating a superior fit compared to the PFO model. Based on these findings, the PSO model was considered appropriate for explaining the adsorption mechanism and it was determined that the chemisorption mechanism governed the adsorption process, as previously reported [53].…”
Section: Kinetics Studymentioning
confidence: 94%
“…The characteristic peaks of Pb 4f and Cu 2p are visibly observed for SSN-Pb and SSN-Cu, respectively (Figure 10a-c), indicating that the Pb and Cu cations have attached to the surface of SSN. In addition, the characteristic peaks of the -NH3 + (401.94 eV) and -NH2 (399.74 eV) groups in the N 1s pattern (Figure 10d) had shifted slightly in terms of higher energy, which could be attributed to the complex reaction between these nitrogencontaining groups and the heavy metal cations [17]. The weakening of the adsorption peak for the -NH-group (694 eV) was attributed to the surface-covering Pb (or Cu) atoms in the adsorbent.…”
Section: Mechanisms For Sorptionmentioning
confidence: 99%
“…2− [17][18][19]. Meanwhile, a previous study has demonstrated the viability of ammoniation modification for SiO 2 , indicating its effectiveness [12].…”
Section: Introductionmentioning
confidence: 96%